Incremental benefits from the increasing in the production of koi fish Cyprinus carpio var. koi culture - Iis Diatin; Dini F Nuristy; Ahmad Teduh; Muhammad Mujahid (Jurnal Akuakultur Indonesia)
ABSTRACT